Sistema de control de existencias y facturas en la planta de cárnicos de la Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López - Cedeño Santana, Karina Lisbeth (2013)
In order to improve business management and billing was developed and implemented an inventory and invoices control system in the Meat Plant of the Agricultural Polytechnic School of Manabí Manuel Félix Lopez, because the processes were performed with delayed using physical Kardex and was considered necessary to implement a control system for controlling inventory and billing costs and the movement of income, expenses and billing. To do this, an interview was conducted to the administrator to determine the requirements that for developing the software. The system uses the programming languages Visual Studio 2010 and SQL Server 2008, which permitted to run the application providing better control and efficiency to the processes by which the Scrum methodology was developed in phases. The setup was acceptable contributed to optimize the time of admission in records for products, materials, customers, suppliers and the cost benefit, among others.